Modified Keystone a Versatile Flap Reconstruction for Mastectomy Defects: Our Clinical Experience - Anastasia Dessy Harsono; Dominic Melino Tjokrovonco; Birgita Maria Ratu Rosari Bas; Pratama Mandala Putra (Indian Journal of Plastic Surgery)
Introduction The closure of extensive defects in reconstructive surgery is a common challenge. The keystone flap technique has gained popularity due to its adaptability and reliance on fascia, providing a reliable blood supply and offering a better match for skin color compared with skin grafts. However, keystone flap necrosis can occur due to tension and inadequate tissue perfusion. To address this, a modified keystone flap technique called the “doubled-handle saucepan” was developed, resulting in improved flap vitality and reduced tissue necrosis, particularly in mastectomy defects.